Atomic‐Scale Structure and Properties of Epitaxial PbZr0.2Ti0.8O3/SrRuO3 Heterointerfaces. Issue 8 (21st April 2015) - Mi, Shao‐Bo; Jia, Chun‐Lin; Vrejoiu, Ionela; Alexe, Marin; Hesse, Dietrich
Abstract : The depolarization effect at the interfaces between PbZr0.2 Ti0.8 O3 and SrRuO3 film layers and 180° domains in the PbZr0.2 Ti0.8 O3 film layer are characterized, demonstrating that the polarization bound charges induced at the interfaces are not completely compensated by the charge carriers in the SrRuO3 electrode layer. Chemical intermixture at interfaces may have a role in incompletely compensating the bound charges.